(3QSGdI aj GdOhGFQ GdJi JMO GdSGYGJ GdReGfjI hHYV eG jJUd HYed GdESWQdGHs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3SCdJ CjOc Gddg Yf GdOhGFQ GdeQSheI ai SWM GdGSWQdGH Ydi eHGOF GdSGYGJ GdReGfjI abdJ gd jUM GdYed HgG ai SGFQ GdeOGQGJ GdJi djSJ eQSheI ai SWMI Ce dG s
(3BNQgG (B:s
(3abO hVM dc UMI eG PcQg CHh eMeO GdSjai Ydi ZjQ GdWQjb ef JbOe ai GdHQgGf hGdJQJjH hGdMeO ddg QH GdYGdejf s
(3HYK HgG GdeDda Edi CHj GdQjMGf GdHjQhfis
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs